The side effects of safe asset creation - Sushant Acharya; Keshav Dogra (Federal Reserve Bank of New York, 2018)
We present an incomplete markets model to understand the costs and benefits of increasing government debt in a low interest rate environment. Higher risk increases the demand for safe assets, lowering the natural rate of interest below zero, constraining monetary policy at the zero lower bound, and raising unemployment. Higher government debt satiates the demand for safe assets, raising the natural rate and restoring full employment. While this permanently lowers investment, a policymaker committed to low inflation has no alternative. Higher inflation targets, instead, permit both full employment and high investment, but allow for harmful bubbles. Aggressive fiscal policy can prevent bubbles.
Keywords: E3; E4; E5; G1; H6; 330; safe assets; negative natural rate; crowding out; risk premium; liquidity traps; bubbles